2021
DOI: 10.4046/trd.2020.0139
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Worsening Oxygenation in Patients with Non-severe COVID-19 Pneumonia

Abstract: Background This study aimed to determine the parameters for worsening oxygenation in non-severe coronavirus disease 2019 (COVID-19) pneumonia. Methods This retrospective cohort study included cases of confirmed COVID-19 pneumonia in a public hospital in South Korea. The worsening oxygenation group was defined as that with SpO 2 ≤94% or received oxygen or mechanical ventilation (MV) throughout the clinical course versus the non-worsening oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Previous studies showed several factors are associated with the deterioration of the disease and the poor outcome, including older age, male, comorbidities such as obesity, hypertension, heart disease, chronic obstructive pulmonary disease, and chronic kidney disease, and also laboratory parameters such as C-Reactive Protein and NLR. 3,8,10,[20][21][22][23][24] In our study, age over 60 years old, previous history of heart disease, diabetes mellitus, respiratory rate > 23x/minute, and NLR value > 3.8 were found to be statistically significant as the factors affecting the worsening of COVID-19 in multivariate analysis. Several conditions may affect the results.…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies showed several factors are associated with the deterioration of the disease and the poor outcome, including older age, male, comorbidities such as obesity, hypertension, heart disease, chronic obstructive pulmonary disease, and chronic kidney disease, and also laboratory parameters such as C-Reactive Protein and NLR. 3,8,10,[20][21][22][23][24] In our study, age over 60 years old, previous history of heart disease, diabetes mellitus, respiratory rate > 23x/minute, and NLR value > 3.8 were found to be statistically significant as the factors affecting the worsening of COVID-19 in multivariate analysis. Several conditions may affect the results.…”
Section: Discussionsupporting
confidence: 47%
“…Another important issue that is often omitted in epidemiological and ML studies of COVID-19 is the close correlation of many predictors to age and sex, two inherent features of every patient. The investigations comparing the age- and sex-matched patients using ML approaches are currently limited to the deep profiling of circulating proteins (including cytokines), lipids, metabolites, and miRNA collected before or around the time of hospital admission and predicting the COVID-19 positivity [ 28 , 29 , 30 , 31 ] or disease severity [ 30 , 31 , 32 , 33 , 34 , 35 ], too small single-center studies of coagulation/fibrinolysis markers in predicting mortality [ 36 ], and to the studies of the lung computed tomography images [ 37 ] or electrocardiograms [ 38 ] to diagnose [ 37 ] or exclude [ 38 ] COVID-19. The matching of study cohorts by age and sex reduces the background behind the risk factors and clarifies the pathophysiological links between the comorbidities, organ damage, and serum biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The CFR among critical cases was 49% and patients with older age and comorbids are factors that can increase the mortality of COVID-19 patients 7 . The severity of the disease in COVID-19 patients generally occurs 1 week after the appearance of symptoms 8,9 .…”
Section: Introductionmentioning
confidence: 99%